Macromol. Chem. Phys. 13/2017. Issue 13 (July 2017) - Sampson, Kathleen L.; Lessard, Benoît H.; Cho, Eunjung; Bender, Timothy P.
Abstract : Front Cover : Solution‐processable, semiconducting organic materials are desirable for scaling the production of organic electronics. Having a handle on the thermal transition temperatures of the polymeric material is essential for certain fabrication steps. The unique photophysical properties of boron subphthalocyanine (BsubPc)‐containing polymers are explored to demonstrate how the BsubPc semiconducting moiety effects the solid‐state arrangement and glass transition temperature. This is reported by Kathleen L. Sampson, Benoît H. Lessard, Eunjung Cho, and Timothy P. Bender* in article number1600592 .